Innovation in natural resource-based industries: A pathway to development? Introduction to special issue - Andersen, Allan Dahl (2018)
Despite growing academic attention to the relationship between economic development and natural resources in social sciences, the issue has received rather limited attention in the field of Innovation Studies. This is problematic given the centrality of innovation and technological change for growth and development. Against this background, this introductory article aims to make four contributions. First, to assess the extent to which Innovation Studies has analysed the link between natural resources and development. Second, based on recent studies of innovation in natural resource-based industries (NRBIs), we elaborate on and articulate an innovation and industry perspective on the relationship between natural resources and development. In this, we foreground the particularities of innovation in NRBIs. Third, we explore policy implications of the specificities of innovation in NRBIs. It matters greatly for design and choice of policy instruments in support of innovation and development whether and how innovation in NRBIs differ from innovation in other industries. Lastly, we introduce the papers constituting this Special issue and propose avenues for further research.